Analysis of Nepalese post graduate students’ errors in writing research proposals - Pitambar Paudel (Universitas Pendidikan Indonesia, 2022)
With the change in socio-political and educational contexts in global academia, the trend of writing academic papers has arisen among Nepali students and educators in higher education. However, many of them are still unfamiliar with the basic standard to be incorporated in an academic paper. In this context, this study examined the post-graduate students’ errors in writing research proposals. A textual analysis method was employed, where quantitative phase of analysis was followed by qualitative, and the data were collected from 24 purposively selected research proposals and from the interview with 10 students. The quantitative data were gathered from content analysis of the research proposals and qualitative data were collected from the unstructured interview. The collected proposals were studied, erroneous expressions were listed and categorized in to four parameters like grammatical errors, lexical semantic errors, mechanic errors and syntactic errors. The information from the interview was recorded, noted and analyzed. The results exhibited that (1) article and preposition usages were more persistent grammatical errors; (2) run-ons and fragmentation were more reiterated syntactic errors; and (3) uses of single lexical items were more common lexical-semantic errors and punctuation was the more regular mechanical errors. These findings reveal that students have insufficient knowledge and skills for academic writing. Therefore, they need academic writing courses, training, or workshops from the early level of their schooling. The findings of this study are useful for curriculum designers, policymakers, instructors, and students because it provides significant information on the building blocks experienced by English language learners in writing research paper.